The influence of lifestyle habits on quality of life in patients with established rheumatoid arthritis—A constant balancing between ideality and reality - Malm, Karina (Int J Qual Stud Health Well-being, 2016)
INTRODUCTION: Rheumatoid arthritis (RA) is a chronic, inflammatory, and systemic disease with symptoms that limit activities and affect quality of life. RA is associated with an increased risk of developing comorbidities, some of which are also known to be associated with lifestyle habits such as physical activity, diet, smoking, and alcohol. There has been an augmented focus on the implementation and maintenance of healthy lifestyle habits even for patients with RA in the past decade, but little is known about the link between patients’ experiences of lifestyle habits and quality of life. The aim of the study was thus to describe and explore how patients with established RA experience the influence of lifestyle habits on quality of life. METHODS: The study had a descriptive and explorative design, based on qualitative content analysis. Strategic sampling was used in order to achieve variations in experiences. Twenty-two patients with RA (14 women and 8 men) from 30 to 84 years old, with a disease duration ranging from 8 to 23 years, were interviewed. RESULTS: The analysis of the influence of lifestyle habits on quality of life resulted in the theme balancing between ideality and reality. Three categories emerged about how lifestyle habits influenced quality of life by limitations (including insufficiency and adaptation), self-regulation (including guilt and motivation), and companionship (including belonging and pleasure). CONCLUSIONS: Quality of life for patients with established RA was influenced by the balance between ideality and reality in the lifestyle habits: physical activity, diet, smoking, and alcohol. This is important new knowledge for health professionals when discussing lifestyle habits with RA patients.